Analyzing the Components of Enhancing Dyadic Ego Strength (Facilitating the Transition from "I-ness" to "We-ness" in Marital Relationships) for Married Individuals - Sadeghi , Zahra; Atashpour, Seyed Hamid; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of the present study was to analyze the components of enhancing dyadic ego strength (facilitating the transition from "I-ness" to "We-ness" in marital relationships) specifically for married individuals. The research setting included all texts related to the concept of "We-ness." Methods: The method for selecting texts was purposive sampling from among the aforementioned texts or related constructs within the time frame of 2010 to 2025, based on inclusion and exclusion criteria. The number of texts was determined according to the principle of data saturation. Data collection involved line-by-line analysis of texts based on questions relevant to the concept of "We-ness." The data obtained from the textual analysis were analyzed using the conventional content analysis method proposed by Hsieh and Shannon (2005). Findings: Content analysis of the texts revealed that dyadic ego consists of four key concepts: (1) essence (with sub-concepts of attention to marital union and dyadic identity); (2) dimensions of dyadic ego (with sub-concepts of cognitive, positive emotional, negative emotional, and behavioral aspects); (3) pathways to achieving dyadic ego (with sub-concepts of generative meaning of the marital bond, family values, and family goals); and (4) obstacles to achieving dyadic ego (with sub-concepts of individualism, lack of self-differentiation, and insecure attachment). Conclusion: Based on these findings, it can be concluded that dyadic ego is a mechanism that transforms the process of "I-ness" into "We-ness," and for its realization, couples must engage in pathways to attain it and overcome its obstacles.